Project-Based Learning Through a Heutagogic Approach in Higher Education: Challenges, Technology and Implementation - Sutarjo Sutarjo; Acep Bahrum Kamil Acep Bahrum Kamil; Sya'roni Ma'shum Ma'shum; Wafa Haifa Zahra; Muhamad Taufik Bintang Kejora; Ade Irvi Nurul Husna (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study explores the implementation of Project-Based Learning (PBL) with a heutagogic approach in universities to enhance student autonomy and critical thinking. An explanatory sequential mixed-methods design was used, combining quantitative surveys with qualitative interviews, observations, and document analysis. The study involved 150 students from three universities in West Java. Quantitative data were analyzed using descriptive statistics in IBM SPSS 24, while qualitative data were examined through thematic analysis and triangulation techniques. Findings indicate that PBL with a heutagogic approach follows seven systematic steps: problem identification, learning objective formulation, project strategy planning, information collection, project execution, presentation of results, and reflection. This method significantly enhances students’ critical thinking, creativity, and independent learning skills. However, challenges include limited technological resources, the need for more structured lecturer guidance, and student time management issues. Technological tools such as Google Classroom, Zoom, and presentation software support PBL effectiveness, though unequal access to technology remains a constraint. Addressing these challenges requires institutional investment in infrastructure, faculty training, and policy development to foster autonomous and collaborative learning environments. The findings provide insights for higher education institutions on optimizing heutagogic-based PBL to develop graduates equipped with the skills needed in the modern workforce.